A simple sensor based on 1, 8-naphthalimide with large Stokes shift for detection of hypochlorous acid in living cells. Issue 54 (1st October 2019) - Jiao, Chunpeng; Liu, Yuanyuan; Lu, Wenjuan; Zhang, Pingping; Ma, Xia; Wang, Yanfeng
Abstract : Probe 1 shows excellent selectivity to HOCl among different ions including common ROS, high sensitivity, high fluorescence quantum yield ( Φ = 0.93), low detection limit (0.237 μM) and successfully used for the detection of HOCl in cells. Abstract : Hypochlorous acid (HOCl), one of the most reactive and deleterious reactive oxygen species (ROS), plays a vital role in many pathological and physiological processes. However, as a result of the highly reactive and diffusible nature of HOCl, its uncontrolled production may lead to an adverse effect on host physiology. Because of its biological importance, many efforts have been focused on developing selective fluorescent probes to image HOCl. However, it is still challenging to design a fluorescent probe with exclusive selectivity towards HOCl. In this study, a novel fluorescent probe for HOCl, Probe 1 was rationally designed based on 1, 8-naphthalimide. As the concentration of HOCl increased, the fluorescence intensity of the probe gradually decreased, and the solution color changed from yellow-green to colorless, indicating this is a "naked-eye sensor". Probe 1 has a large Stokes shift (120 nm), which can effectively avoid fluorescence self-absorption. In addition, Probe 1 shows excellent selectivity to HOCl among different ions including common ROS, high sensitivity, fast response (<2 min), high fluorescence quantum yield ( Φ = 0.93) and low detection limit (0.237 μM). Finally, the imaging results in HeLa cells showed that the probe could be used for the detection of exogenous and endogenous HOCl, and proved the potential of the probe as a biosensor for the detection of HOCl.